Idiopathic Pulmonary Comorbidities and Mechanisms - Maricica Pacurari; Amal Mitra; Timothy Turner (International Journal of Inflammation)
Idiopathic pulmonary fibrosis (IPF) is a disease with an unknown etiology mainly characterized by a progressive decline of lung function due to the scarring of the tissue deep in the lungs. The overall survival after diagnosis remains low between 3 and 5 years. IPF is a heterogeneous disease and much progress has been made in the past decade in understanding the disease mechanisms that contributed to the development of two new drugs, pirfenidone and nintedanib, which improved the therapeutic management of the disease. The understanding of the cofactors and comorbidities of IPF also contributed to improved management of the disease outcome. In the present review, we evaluate scientific evidence which indicates IPF as a risk factor for other diseases based on the complexity of molecular and cellular mechanisms involved in the disease development and of comorbidities. We conclude from the existing literature that while much progress has been made in understating the mechanisms involved in IPF development, further studies are still necessary to fully understand IPF pathogenesis which will contribute to the identification of novel therapeutic targets for IPF management as well as other diseases for which IPF is a major risk factor.